Women Education in India and Economic Development Linkages: A Conceptual Study - Azra Khan; Shayista Majeed; Rayeesa Sayeed (International Journal of Engineering and Management Research, 2020)
Women have been recognised as a crucial force in economic development of any nation. However, it is imperative to mention that traditionally their lives were confined to the four walls of the house. They were mainly engaged in household chores, bearing and rearing of children and were treated on different footings. Their existence was deeply influenced by the prevailing patriarchal system which often results into deprivation of their basic rights as enjoyed by their male counterparts including their right to education. But, with the advent of various legislations, social reforms and women’s movement worldwide, there was a major shift in the socio-cultural set up and women’s entitlement to education begun to be recognised as pivotal for nations’ economic development. On the other hand, history has revealed that in Indian sub-continent, there was a worst scenario of women education. Women were denied their basic right to education and such bias was deeply rooted in prevailing socio-cultural set up where females were treated inferior to men. But, in the backdrop of various social reform movements, women movements, Christian missionaries and new economic reforms of 1991 popularly called as LPG concept (Liberalization, Privatization and Globalization), women education in India witnessed a drastic change. Further, research has noted a strong positive linkage between women education and economic development of any nation. Thus, keeping in view the importance of women education for an economic development of a nation, the present study is an endeavour towards identifying, reviewing and analysing the prior work with respect to above linkages. Moreover, the study has also identified the various issues pertaining to women education in India which has remained unaddressed and demands utmost attention. At the end of the study, various valuable suggestions have also been drawn in order to fill the identifiable gaps in women education structure so as to change its state and enhance its contribution towards achieving robust economic development.